Financial Accounting - Valix,Conrado T. (Manila : GIC Enterprise, 2009)
This book is the culmination of the Financial Accounting cluster. It is designed to cover the preparation of statement of financial position, income statement, statement of comprehensive income, statement of changes in equity, statement of cash flows and notes to financial statements.
Financial statements 1 -- Statements of financial position 29 -- Notes to financial statements 97 -- Statement of comprehensive income 139 -- Noncurrent asset held for sale discontinued operation 197 -- Accounting changes 228 -- Interm financial reporting 270 -- Operating segment 304 -- Cash basis and accrual basis 350 -- Single entity 392 -- Error correction 430 -- Statement of cash flows 471 -- Hyperinflation 545.
Keywords: ACCOUNTING